Analisis Kedudukan Badan Hukum dari Firma - Rusli, Hardijan (LAW REVIEW, 2001)
Firma or vennootschap onder Firma is a partnership form which is frequently used by investors. Firma is governed by the commercial code and the provisions of the Maatschap contained in the civil code. Maatschap is a contract law not a partnership form law so it is dellned as a contract whereby two or more persons agree to contribute something together, to carry on a business together, in order to share in the profits accruing from the effort. Maatschap is a contract law that governs those who carry on business together usually deemed as a partnership form. Firma is not defined as a contract but as a partnership form used for traders and businessmen. Maatschaap is not a legal entity nor a legal partnership form. In the Maatschap, partners are not bound to each other because Maatschaap is not a legal partnership form nor a legal entity. A partner of Maatschap will bind other partners if only they have given power of attorney or their business has got the benefits of the transaction. In the Firma, each partner has the right to act in the name of the Firma within the scope of its activities and it binds the Â Firma (entity) but each partner, in the Firma, is responsible for each and every liability of the Firma toward third parsons. Even though each partner can bind the Firma (entity), many lawyers still deem that the Firma is not a legal entity because each partner as legal subject of natural person has responsibility of each and every the Firmas liability. It seems that the Firma is not a legal entity but only as legal subject of natural person Â because each partner has the responsibility to pay off the Firmas liability. The matter that scholars are still arguing until nowadays is whether Firma is a legal subject (entity) ?Â